ANALYSIS OF THE APPLICATION OF PATIENT SAFETY CULTURE IN PRABUMULIH CITY HOSPITAL, SOUTH SUMATERA, INDONESIA - Pitri Noviadi; Sulastri Sulastri (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2022)
Prabumulih City Hospital Accreditation graduation predicate in 2019 which decreased from fully accredited to mid-accredited, where one of the working groups that had not passed was the facility management and safety working group with a score of 67.62. This is also supported by data from the results of recording patient safety incidents for 3 consecutive years from 2018 to 2020. Departing from this problem, the authors are interested in conducting research on "Analysis of the Application of Patient Safety Culture in Prabumulih City Hospital in 2021. " The purpose of this study was to determine and analyze the application of patient safety culture and the factors that influence patient safety culture at Prabumulih City Hospital in 2021. This research is a quantitative study conducted in June and July 2021 on employees of the Prabumulih City Hospital. The sample in this study amounted to 252 people. Sampling was carried out using the stratified random sampling method with the research instrument being a questionnaire. The data were tested using univariate analysis, bivariate chi-square, and multivariate logistic regression. The results of the chi-square test showed that there is a significant relationship between Patient Safety Culture and the 8 independent variables studied, while the variables are age, gender, education level, employment status, work experience, type of work, income, and resources. Based on the multivariate analysis, it was found that the dominant variable that most influenced the application of patient safety culture was the resource variable, with an ap value of 0.000 <0.05 and the largest OR value of 84.564 meaning that the resource variable had 84.564 times the opportunity to influence the patient safety culture at the Prabumulih Hospital in 2021. In conclusion, there is a significant and dominant relationship between the resource variable and the application of patient safety culture at the Prabumulih City Hospital in 2021.